DAMPAK KEBERADAAN ATRAKSI WISATA MANDI SAKRAL DI KAWASAN PURA SURANADI TERHADAP EKONOMI MASYARAKAT - PRAYITNO, JOKO (Tourism, Hospitality And Culture Insights Journal, 2024)
Lombok is one of the tourist destinations in Indonesia which has many tourist attractions. The sacred bathing tourist attraction in Suranadi Temple area is one of them. From my observations, tourists visiting this area not only carry out rituals, but tourists also enjoy traditional culinary delights with basic objectives, reasons, and argumentative factors. The existence of this tourist destination has an impact on the economic aspect. Based on observations, literature studies, and interviews with several residents and temple managers, the findings strengthen the community's view that tourism can have an impact on the economic growth of the Suranadi community.   Keywords: Economy, sacred bath, Suranadi.